2015
DOI: 10.20460/jgsm.2015915624
|View full text |Cite
|
Sign up to set email alerts
|

The Mediator Effect of Foreign Direct Investments on the Relation Between Logistics Performance and Economic Growth

Abstract: Economic growth is a process of enhancement in total production level measured by absolute and relative increases or real production per capita. Economic growth is also related with development of production capacity. Recent researches consider Gross Domestic Product (GDP) as one of the indicators of growth. Logistics Performance Index (LPI) issued by World Bank is an indicator of logistics performance of a country consisting of six dimensions. Foreign Direct Investments involve establishing operations or acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 6 publications
1
7
0
2
Order By: Relevance
“…Hence, it can be concluded that this research's findings can help us understand that FDI cannot influence unemployment rate directly; however, after it is mediated by economic growth and provincial wage rate, FDI can influence the unemployment rate in Indonesian labor market. These findings are in line with the previous studies (Badr and Ayed, 2015;Çelebi et al, 2015;Mahmood, 2015;Nordin et al, 2015;Nwankwo & Igweze, 2016).…”
Section: Path Analysis For Indirect Effectssupporting
confidence: 93%
See 1 more Smart Citation
“…Hence, it can be concluded that this research's findings can help us understand that FDI cannot influence unemployment rate directly; however, after it is mediated by economic growth and provincial wage rate, FDI can influence the unemployment rate in Indonesian labor market. These findings are in line with the previous studies (Badr and Ayed, 2015;Çelebi et al, 2015;Mahmood, 2015;Nordin et al, 2015;Nwankwo & Igweze, 2016).…”
Section: Path Analysis For Indirect Effectssupporting
confidence: 93%
“…Shrout & Bolger (2002) and stated that mediation happens when the causal effects of some X variables on Y results can be explained by M as mediating variable. Studies on the influences of mediating variables in economy were conducted by Badr and Ayed, 2015;Çelebi et al, 2015;Mahmood, 2015;Nordin et al, 2015;Nwankwo & Igweze, 2016. Based on the explanation above, the further objective of this research is to determine what kind of mediating variable will be found; and whether the mediator fully or partially mediate the relationship in this research.…”
Section: Introductionmentioning
confidence: 99%
“… Martí et al (2014) used a gravity model finding that improvements in any of the components of the LPI are positively associated with trade flows, and highlighting that the efficiency and quality of logistics operations do matter. Çelebi et al (2015) confirmed that Foreign Direct Investment (FDI) plays a mediator role in the LPI-economic growth nexus. Khan et al (2017a) collected LPI and GDP data for 15 selected global ranked logistics countries showing that logistics competence and infrastructure boost economic growth and sectoral value added.…”
Section: Literature Reviewmentioning
confidence: 83%
“…Looking at the most recent literature, a first strand of the literature investigated the linkages among logistics performance and economic growth, often including trade ( Coto-Millán et al, 2013 ; Martí et al, 2014 ; Çelebi et al, 2015 ; Khan et al, 2017a , 2017b , 2017b ; Munim and Schramm, 2018 ; Sharipbekova and Raimbekov, 2018 ; Tang and Abosedra, 2019 ; Töngür et al, 2020 ). Under the current context of just-in-time production systems, improving the logistics operations (in terms of border management, quality of services, and tracking of products) reduces the cost of delivery whilst strengthening its reliability and predictability ( Munim and Schramm, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that logistics performance and global connectedness exert influence on human development in an increasingly globalizing world. Studies find logistics performance as being an important antecedent of economic growth, especially with its indirect role played via foreign direct investment and technological advancement (Chu, 2012;Munim and Schramm, 2018;Çelebi, 2018;Çelebi and Oktayer 2018;Çelebi et al, 2015). Foreign direct investment is seen as a primary indicator of global integration and connectedness (Dreher et.…”
Section: Introductionmentioning
confidence: 99%